Activating Transcription Factor 3-mediated Chemo-intervention with Cancer Chemokines in a Noncanonical Pathway under Endoplasmic Reticulum Stress - Park, Seong-Hwan (American Society for Biochemistry and Molecular Biology, 2014)
The cell-protective features of the endoplasmic reticulum (ER) stress response are chronically activated in vigorously growing malignant tumor cells, which provide cellular growth advantages over the adverse microenvironment including chemotherapy. As an intervention with ER stress responses in the intestinal cancer cells, preventive exposure to flavone apigenin potentiated superinduction of a regulatory transcription factor, activating transcription factor 3 (ATF3), which is also known to be an integral player coordinating ER stress response-related gene expression. ATF3 superinduction was due to increased turnover of ATF3 transcript via stabilization with HuR protein in the cancer cells under ER stress. Moreover, enhanced ATF3 caused inhibitory action against ER stress-induced cancer chemokines that are potent mediators determining the survival and metastatic potential of epithelial cancer cells. Although enhanced ATF3 was a negative regulator of the well known proinflammatory transcription factor NF-κB, blocking of NF-κB signaling did not affect ER stress-induced chemokine expression. Instead, immediately expressed transcription factor early growth response protein 1 (EGR-1) was positively involved in cancer chemokine induction by ER stressors. ER stress-induced EGR-1 and subsequent chemokine production were repressed by ATF3. Mechanistically, ATF3 directly interacted with and recruited HDAC1 protein, which led to epigenetic suppression of EGR-1 expression and subsequent chemokine production. Conclusively, superinduced ATF3 attenuated ER stress-induced cancer chemokine expression by epigenetically interfering with induction of EGR-1, a transcriptional modulator crucial to cancer chemokine production. Thus, these results suggest a potent therapeutic intervention of ER stress response-related cancer-favoring events by ATF3.